Lowering light intensity while extending photoperiod at a constant daily light integral synergistically interacts with warm temperature to enhance leaf expansion and crop yield in lettuce in the absence of far-red light - Jeong, Sang Jun; Zhen, Shuyang; Zhang, Qianwen; Niu, Genhua (Frontiers in Plant Science, 2025)
IntroductionLow light intensity and far-red (FR) light act as shade signals to induce specific morphological changes mediated by plant photoreceptors phytochromes (PHYs). Applying FR light or lowering light intensity over a longer photoperiod at a constant daily light integral (DLI) can increase crop yield by enhancing leaf expansion and photon capture. However, PHY activity is also dependent on temperature. We aimed to investigate the interactive effects of FR light, light intensity, photoperiod, and temperature on plant growth and morphology.MethodsLettuce (Lactuca sativa L.) ‘Rex’ was grown under three temperatures (20, 24, and 28 °C), each containing six light treatments [two levels of FR light (0 and 20% FR in total photon flux density from 400-800 nm) x three light intensities (150, 200, and 300 μmol m-2 s-1)]. As light intensity increased, photoperiod was reduced (150, 200, and 300 μmol m-2 s-1 with photoperiods of 24 h, 18 h, and 12 h, respectively) to maintain a constant DLI of 13 mol m-2 d-1.ResultsUnder 0% FR light, the combination of lower light intensity/longer photoperiod and warmer temperature synergistically enhanced leaf expansion and photon capture; however, this interactive effect disappeared under 20% FR light. Stem elongation exhibited an opposite response pattern to leaf expansion; lower light intensity and warm temperature had a synergistic enhancement on stem elongation under 20% FR light, but not under 0% FR light. Shoot dry weight responded to the light and temperature factors similarly to total leaf area. Our results showed that plant biomass accumulation depended primarily on photon capture (r2 = 0.93), rather than single-leaf photosynthetic efficiency. Antioxidant capacity was generally reduced by lower light intensity and FR light, but the reduction could be compensated by warmer temperatures.DiscussionThus, we concluded that applying lower light intensity over a longer photoperiod, combined with warm temperature, can effectively maximize leaf expansion and crop yield while maintaining nutritional quality in the absence of FR light. However, under strong shade signals composed of FR light, low light intensity, and warm temperature, lettuce prioritizes stem elongation at the expense of leaf expansion, leading to reduced crop yield.